Enhanced detection of bacteremia with a new BACTEC resin blood culture medium. - Appelbaum, P C (1983)
In this multicenter study, 621 sets of blood culture specimens were drawn from 280 patients who were suspected of being septic and who were receiving antimicrobial therapy. Equal volumes of each specimen were inoculated into BACTEC 6B and 16B media. The 16B medium contained adsorbent and cationic resins for neutralizing the effects of the drugs. Of the 621 sets drawn, there were 72 positive cultures in 16B and 52 positive cultures in 6B. In 23 cases the organism was detected only in the 16B medium, and in 3 cases the organism was detected in 6B only. The remaining 49 positives were detected in both culture bottles. In 13 of these 49 cultures, detection in 16B was made between 1 and 5 days earlier than in 6B, whereas 3 of 49 specimens were detected 1 day earlier in 6B; the remaining 33 cultures became positive at approximately the same time in both media. There were a total of 43 patients with positive cultures in this study. Of these patients, 28 had sepsis detected in both the 16B and 6B media. The 6B medium alone detected an additional three cases of sepsis, and the 16B resin medium alone identified 12 additional cases. Supplementary culturing of samples from patients receiving antimicrobial therapy significantly increased the number of positive cultures and positive patients, as well as significantly shortening the time to positivity in these cultures.